Circulating tumor DNA fraction predicts residual cancer burden post-neoadjuvant chemotherapy in triple negative breast cancer - Naing Lin Shan; Billie Gould; Xiaohong Wang; Giancarlo Bonora; Kim Blenman; Julia Foldi; Gerson Espinoza Campos; Myles Walsh; Pan Du; Lajos Pusztai (The Journal of Liquid Biopsy)
Purpose: Pathologic response after preoperative/neoadjuvant chemotherapy (NAC) is a continuum that can range from complete pathologic response (pCR) to extensive residual disease (RD). We hypothesized that post-NAC plasma circulating tumor DNA (ctDNA) fraction (TF) reflect pathologic response as continuum measured by the residual cancer burden (RCB) score. Methods: ctDNA was assessed using the PredicineBEACON assay, that interrogates up to 50 personalized tumor variants and 500 hot-spot mutations, in 3 mL archived plasma isolated from EDTA tubes collected post-NAC but before surgery from 44 patients with stage I/III triple negative breast cancer (TNBC) who received durvalumab and weekly nab-paclitaxel followed by doxorubicin/cyclophosphamide on a clinical trial (NCT02489448). Circulating free tumor DNA methylation profiling was performed using PredicineEPIC assay in paired pre- and post-NAC plasma (N = 30). Youden's J-statistics was used to define optimal thresholds. Results: We observed a significant positive correlation (r = 0.45, p = 0.004) between RCB scores and post-NAC TF. The median TF was significantly lower in pCR (RCB0) compared to RD patients (0.06 % vs. 0.3 %, p = 0.02). Using a TF positivity threshold of ≥0.05 %, PredicineBEACON had 58 % sensitivity at 83 % specificity for identifying RD. TF was higher in patients who experienced recurrence (n = 9) compared to those without recurrence (n = 35) (0.17 % vs. 0.05 % TF, p = 0.029). There was significant decrease in methylation signal in post-compared to pre-NAC samples, but post-treatment methylation signal was lower in cases with pCR vs RD. Conclusions: Post-NAC plasma tumor fraction and change in tumor-derived methylation signal predict the extent of RD and recurrence in TNBC patients.